Proposta de sequência didática para o ensino de eletrostática na rede regular de ensino - BARBOSA, Arisandra Cristina Corrêa (2025)
In many cases, Physics teaching in schools ends up not meeting the expectations of students, lacking attractive classes and having a very content-based nature, this teaching is often taken out of the context in which it is applied and ends up focusing on memorizing equations. This approach seems somewhat inadequate for this science, since it presents knowledge as absolute and immutable, disregarding the relative nature of facts, and failing to stimulate students' creativity and critical thinking. To address these issues, this monograph proposes an innovative teaching didactic sequence for high schools, using interactive games, handcraft experiments with alternative materials, and computer simulations, all of which are applied to the learning of electrostatics in third-year high school classes. The proposal was applied to three classes of a regular school in the city of Abaetetuba-PA, to teach electrostatics and increase student engagement, promoting their active participation in the learning process. Based on the results obtained through questionnaires applied before and after the application of the didactic sequence, we observed that student learning improved considerably, showing that the use of different approaches to the same topic is fundamental in teaching, as the implementation of these actions promoted more effective learning, being a great alternative for basic education teachers, in the minimization of the students' learning difficulties.